Evaluation of the Effect of Betulin and Its Alkynyl Derivatives on the Profile of Changes in Gene Expression of the Inflammatory Process of Colorectal Adenocarcinoma Cells (HT-29 Cell Line) - Lubczyńska, Agnieszka; Bębenek, Ewa; Garncarczyk, Agnieszka; Wcisło-Dziadecka, Dominika (Processes, 2023)
Betulin is a lupane-type pentacyclic triterpene. It is characterized by a range of biological properties, including anti-cancer and anti-inflammatory activities. It is also an origin compound for obtaining derivatives with higher biological activity and better bioavailability. Chronic inflammation stimulates the formation of a pro-cancer microenvironment, promoting tumor growth, cell migration, and neoangiogenesis. Many factors, immune system cells, and cytokines and chemokines released by them are involved in this process. Therefore, it has been suggested that the optimal target for anti-cancer drugs in this disease could be substances showing anti-inflammatory activity. The aim of the study was to indicate the direction of changes in the expression of genes related to the inflammatory state in colorectal cancer cells promoted by betulin and its selected alkynyl derivatives. Cytotoxicity assessment was carried out using a sulforhodamine B (SRB) test, whereas lipophilicity was determined by reversed-phase thin-layer chromatography (RP-TLC). The analysis of the gene expression profile in colon adenocarcinoma cells treated with betulin and its derivatives was performed using oligonucleotide microarrays HG-U133A. Based on the conducted analysis, it can be stated that betulin and its derivatives 1–3 influence the change in the expression profile of genes related to inflammatory processes in the HT-29 colon adenocarcinoma cell lines. The highest expression changes (FC > 2) were observed for HMOX1 (compound 1 vs. control) and TMED7 (compound 3 vs. control) mRNAs. An important observation is the comparison of the profile of changes in the expression of the studied genes in the compared compounds. Derivative 1 showed the greatest similarity to control cells, whereas betulin showed similarity to cisplatin. These observations indicate the necessity further research on the impact of betulin and its derivatives on inflammatory processes and the possible direction of chemical modification of compounds.